2016
DOI: 10.1016/j.jneumeth.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A linear model for event-related respiration responses

Abstract: HighlightsWe develop a novel method for analysing event-related respiratory responses.This method is based on a Psychophysiological Model (PsPM) of interpolated time series.We analyse respiration period (RP), amplitude (RA) and flow rate (RFR).RA and RFR estimates distinguish different event types, and all three measures distinguish events from non-events.The new method could be useful for fMRI experiments using respiration belts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
(78 reference statements)
0
25
0
Order By: Relevance
“…The second PC resembled a time derivative of the first component. Rather than approximating the second component, we directly computed the time derivate of the gamma response function (SEBRF'), which was included together with the SEBRF into a model M2, analogous to previous models for SCR (Bach et al, ), HPR (Castegnetti et al, ; Paulus et al, ), respiration (Bach et al, ), and fMRI (Friston et al, ). Since the tail of the first PC component was not well fitted by M1 (Figure ), we created a third model M3 that combined the SEBRF with a Gaussian function to model the response tail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second PC resembled a time derivative of the first component. Rather than approximating the second component, we directly computed the time derivate of the gamma response function (SEBRF'), which was included together with the SEBRF into a model M2, analogous to previous models for SCR (Bach et al, ), HPR (Castegnetti et al, ; Paulus et al, ), respiration (Bach et al, ), and fMRI (Friston et al, ). Since the tail of the first PC component was not well fitted by M1 (Figure ), we created a third model M3 that combined the SEBRF with a Gaussian function to model the response tail.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated for SCR, HPR, respiratory measures, and pupil size responses that such implicit assumptions can be made explicit in a psychophysiological model (PsPM). This model specifies, in mathematical form, the expected shape of the response (Bach et al, ; Bach, Flandin, Friston, & Dolan, ; Bach, Gerster, Tzovara, & Castegnetti, ; Korn & Bach ; Paulus, Castegnetti, & Bach, ). The shared variance between expected response with unit amplitude and actual data, assessed, for example, in a regression model, can then be used to quantify response magnitude.…”
mentioning
confidence: 99%
“…For such a GLM, the design matrix is formed by convolving event onsets with the impulse response function with unit amplitude. This approach is commonplace in the analysis of neuroimaging data (Friston, ; Friston, Jezzard, & Turner, ), and has more recently been extended in the form of PsPM to skin conductance responses (SCR; Bach, Flandin, Friston, & Dolan, ), heart period responses (Paulus, Castegnetti, & Bach, ), and respiratory responses (Bach, Gerster, Tzovara, & Castegnetti, ). A similar approach has been used for pupil size measurements related to detecting auditory events (Knapen et al, ) and perceptual decision making (de Gee, Knapen, & Donner, ).…”
mentioning
confidence: 99%
“…Moreover, one study suggested changes in respiratory period and, relatedly, end‐tidal carbon dioxide pressure (PetCO 2 ), as a result of aversive conditioning (Van Diest, Bradley, Guerra, Van den Bergh, & Lang, ). However, we have recently shown that respiration amplitude responses (RAR) may be better suited to distinguish cognitive processes than respiration period (Bach et al, ). This motivates our current study in which we consider a possibility that conditioned changes in RAR may allow assessing fear memory.…”
mentioning
confidence: 99%
“…We capitalize on a previously developed psychophysiological model (PsPM) of event‐related RAR (Bach et al, ), which is formalized as a general linear model (GLM). We first analyze RAR to CS+ and CS− to establish an impulse response function for fear‐conditioned RAR.…”
mentioning
confidence: 99%